High-gain extended Kalman filter for continuous-discrete systems with asynchronous measurements. Issue 8 (2nd August 2020) - Feddaoui, Aïda; Boizot, Nicolas; Busvelle, Eric; Hugel, Vincent
ABSTRACT: This paper investigates an adaptation of the high-gain Kalman filter for nonlinear continuous-discrete system with multirate sampled outputs under an observability normal form. The contribution of this article is twofold. First, we prove the global exponential convergence of this observer through the existence of bounds for the Riccati matrix. Second, we show that, under certain conditions on the sampling procedure, the observer's asynchronous continuous-discrete Riccati equation is stable and also, that its solution is bounded from above and below. An example, inspired by mobile robotics, with three outputs available is given for illustration purposes.